Is Optimism can Reduce Pregnant Pain? - Triwulandari, Desy; Fourianalistyawanti, Endang (Universitas Negeri Padang, 2017)
This study aimed to found the relationship between optimism and pain in pregnant woman. This study was done using associative methods to 116 pregnant mothers underwent pain. Optimism was measured by Life Orientation Test-Revised (LOT-R) Scale developed by Scheier, Carver and Bridges. Then, the pain was measured by Numerical Rating Scale (NRS) developed by McCaffery and Passero. The result of this research indicated that optimism had no significant links with pain in pregnant women. It meant that the higher score of optimism that pregnant women obtained, not always followed by low pain.